Sosialisasi MBKM di Universitas Sahid Surakarta - Yunita Primasanti; Evelyn Henny Lukitasari; Farid Fitriyadi (Lembaga Pengembangan Kinerja Dosen, 2024)
The learning process at the Merdeka Campus is one manifestation of student-centered learning which is very essential. Learning on the Independent Campus provides challenges and opportunities for developing innovation, creativity, capacity, personality and student needs, as well as developing independence in seeking and finding knowledge through the realities and dynamics of the field such as ability requirements, real problems, social interaction, collaboration, self-management, performance demands, targets and achievements. Through a well-designed and implemented independent learning program, students' hard and soft skills will be strongly formed.In the series of introductions to new students, the MBKM team was asked to be a resource for introducing MBKM to new students. The aim of this activity is to provide knowledge to new students regarding MBKM. There are several benefits that students can get by participating in MBKM activities, one of which is additional competency skills outside campus, learning experiences outside campus and recognition of a maximum of 20 credits for MBKM activities so that they can speed up graduation. Students and students have the skills desired by industry.